Flexibilidade e permanência: os edifícios públicos modernos de Fortaleza - Braga, Bruno Melo (2017)
This work aims to analyze the attribute of flexibility as a design strategy to ensure the permanence of buildings. The objective of the analysis is to study four modern public buildings for administrative purposes produced in Fortaleza between 1970 and 1982: the Palace of Abolition (1970), the Headquarters of the General Directorate of DNOCS (1973), the Ministry of Finance (1979), and The Secretary of Education of the State of Ceará (1982). In addition to their architectural value, these buildings have recently undergone interventions, which makes it possible to identify how the flexible spaces of the original designs allowed the alterations, whether of use or technology, not to imply the loss of their essential characteristics. Thus, from a methodology developed based on the theoretical framework on flexibility, categories of analysis were created for application in the chosen works, as well as technical visits, documentation and digital modeling. Finally, the work suggests a dual validity of this theme in contemporary times: both as a strategy for interventions in modern buildings and as a design principle for designing new buildings, as the need for flexible spaces becomes more and more urgent.